2022
DOI: 10.1177/21582440221096136
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Factors and Moderating Effects of Age and Gender That Influence the Intention to Use a Non-Directive Reflective Coaching Chatbot

Abstract: Chatbots are increasingly applied in various contexts including helping professions, such as organizational and life coaching. Coaching facilitates individual wellness, behavioral change, and goal attainment in a reflective, non-directive manner, and is considered one of the fastest-growing professions. The use of knowledge imparting service chatbots have been studied; however, the application of chatbots in coaching has received scant research attention, raising the question about which factors and moderating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 68 publications
2
13
1
Order By: Relevance
“…Hence, service marketers should strive for reducing the PR to customers to encourage them toward adopting CAs. However, studies of [ [23] , [24] ] did not find any significant influence of PR on chatbot adoption intention, which contrasts with the findings of this study. Despite inconsistent results reported by some of the studies, the present study sheds light on the significant evidence of PR associated with CAs in the banking context.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Hence, service marketers should strive for reducing the PR to customers to encourage them toward adopting CAs. However, studies of [ [23] , [24] ] did not find any significant influence of PR on chatbot adoption intention, which contrasts with the findings of this study. Despite inconsistent results reported by some of the studies, the present study sheds light on the significant evidence of PR associated with CAs in the banking context.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the significance of the other constructs was not found in the analysis. Terblanche and Kidd (2022)[ 24 ] PX, EE, FC, SI and PR Adoption intention of coaching chatbot Gender, age PX, SI, and FCs played significant roles as direct factors influencing the intention to use the coaching chatbot. The impact of PE was found to be moderated by gender, while age showed a tendency to moderate the effect of EE.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The study revealed that knowledge about using chatbots and performing various tasks using the conversational agents is essential to enhance the adoption of chatbot technology. This result in fact, concurs with the findings of Terblanche and Kidd (2022).…”
Section: Discussionsupporting
confidence: 93%
“…Venkatesh et al [ 13 ] defined BI as the willingness and readiness of individuals to engage with a particular technology. This intention is often considered a direct precursor to use of the technology [ 22 , 32 ]. Numerous studies, i.e., refs.…”
Section: Literature Reviewmentioning
confidence: 99%